2021
DOI: 10.2147/opth.s294710
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study Between the Goldmann Applanation Tonometer and the Non-Contact Air-Puff Tonometer (Huvitz HNT 7000) in Normal Eyes

Abstract: Objective To assess whether the non-contact air-puff tonometer (NCT) is an appropriate alternative to the Goldmann applanation tonometer (GAT) for measuring intraocular pressure (IOP). Patients and Methods An observational, cross-sectional, and comparative study with a quantitative approach was carried out. Two techniques for IOP measurements using the standard GAT and the NCT were compared. A total of 180 eyes from 90 patients were included in the study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Demirci et al showed that IOP measurements with NCT were significantly higher than those obtained with both GAT and rebound tonometry, with significant differences ( p < 0.001) in all age groups [ 36 ]. A recent study confirmed that NCT tends to overestimate IOP GAT measurements in patients with IOP > 16 mmHg, which was more evident when IOP > 20 mmHg [ 37 ], showing a decrease in accuracy at higher values.…”
Section: Non-contact Tonometry (Air-puff Tonometry)mentioning
confidence: 83%
“…Demirci et al showed that IOP measurements with NCT were significantly higher than those obtained with both GAT and rebound tonometry, with significant differences ( p < 0.001) in all age groups [ 36 ]. A recent study confirmed that NCT tends to overestimate IOP GAT measurements in patients with IOP > 16 mmHg, which was more evident when IOP > 20 mmHg [ 37 ], showing a decrease in accuracy at higher values.…”
Section: Non-contact Tonometry (Air-puff Tonometry)mentioning
confidence: 83%
“…This finding is consistent with that of a previous study, which reported that NCT overestimated IOP in the lower value range and underestimated IOP in the higher value range ( 22 ). However, some studies reported opposite findings, suggesting that IOP NCT values were approximately equal to IOP GAT values in the group with low IOP, while they were overestimated in that with high IOP ( 10 , 23 ). Larger sample sizes are required to validate these results.…”
Section: Discussionmentioning
confidence: 96%
“…Many types of devices have been proposed for IOP measurement, such as Goldmann applanation tonometry (GAT), non-contact tonometry (NCT), ICare rebound tonometer, and dynamic contour tonometer, each of which has advantages and disadvantages ( 8 ). The GAT is widely regarded as the gold standard for IOP measurement due to its accuracy and excellent reproducibility, while NCT is most widely used in outpatients and in ocular hypertension screening because of its non-invasive and convenient nature ( 9 , 10 ). However, all measurements are influenced by the structure and biomechanical properties of the cornea, such as the cornea thickness and hysteresis, as well as systemic factors such as systolic pressure ( 11 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…At that point, the production of air is stopped, and the force required to flatten is recorded and used to calculate IOP. The disadvantages of the NCT are that it becomes less accurate at higher subject IOPs, especially with IOP > 20 mmHg [33]. It is also influenced by corneal properties, similar to GAT [34].…”
Section: Noncontact Tonometrymentioning
confidence: 99%